1989
DOI: 10.1152/ajpcell.1989.256.2.c226
|View full text |Cite
|
Sign up to set email alerts
|

Activation of an apical Cl- conductance by Ca2+ ionophores in cystic fibrosis airway epithelia

Abstract: Cystic fibrosis (CF) airway epithelia express a defect in adenosine 3',5'-cyclic monophosphate (cAMP)-dependent regulation of apical membrane Cl- channels. Recent patch-clamp studies have raised the possibility that Ca2+ -dependent mechanisms for the activation of Cl- secretion may be preserved in CF airway epithelia. To determine 1) whether intact normal (N1) and CF airway epithelia exhibit a Ca2+ -dependent mechanism for activation of Cl- secretion and 2) whether Ca2+ -dependent mechanism for activation of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(69 citation statements)
references
References 24 publications
4
65
0
Order By: Relevance
“…However, ionomycin produces very similar effects (Willumsen & Boucher, 1989) and has been shown to directly elevate intracellular calcium in human nasal epithelium (Murphy, Cheng, Yankaskas, Stutts & Boucher, 1988). No stimulation of cyclic AMP levels by A23187 was seen in our tissues.…”
Section: Discussionsupporting
confidence: 56%
“…However, ionomycin produces very similar effects (Willumsen & Boucher, 1989) and has been shown to directly elevate intracellular calcium in human nasal epithelium (Murphy, Cheng, Yankaskas, Stutts & Boucher, 1988). No stimulation of cyclic AMP levels by A23187 was seen in our tissues.…”
Section: Discussionsupporting
confidence: 56%
“…Vectorial ion transport is greatly affected in many CF epithelia (1). CF cells, unlike normal epithelial cells, do not elicit a net Cl Ϫ secretion when challenged with cAMPelevating agents (20), whereas Cl Ϫ secretion in response to agonists that elevate intracellular Ca 2ϩ is preserved (20)(21)(22)(23). To check the phenotypic characteristics of the original ⌬F508 cells (CFT1) and the cells permanently transfected with ␤gal (CFT1-LC3) or wild-type CFTR (CFT1-LCFSN), we studied the secretory responses of these cells.…”
Section: Resultsmentioning
confidence: 99%
“…ATP/UTP) are greater in CF patients than in normal subjects (9,10). In vitro studies also detected a larger apical Ca 2ϩ i -dependent Cl Ϫ conductance in CF airway epithelia (9,(11)(12)(13). In addition, we recently reported that apical P2Y 2 -R activation promotes greater Ca 2ϩ i mobilization in CF compared with normal human nasal epithelia (4).…”
Section: ؉mentioning
confidence: 89%